A similaridade no uso do microhabitat por girinos (Amphibia, Anura) reflete processos ecológicos ou filogenéticos? - Melo, Lilian Sayuri Ouchi de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Inumerous processes have been suggested to explain the community structure, such as competition, predation, dispersal, continental drift, environmental filtering, speciation. To comprehend the influence of these processes on a local scale provide a better understanding of the composition and species richness determinants in communities, especially physically well defined communities, as is the case of the communities of tadpoles. Our goal in this study was to investigate the influence of environmental characteristics in communities structures of tadpoles in lotic and lentic water bodies. We conducted sampling in an area of Atlantic Rain Forest in southeastern Brazil. This work is divided into two section. In the first chapter we verified which environmental microhabitat characteristics of lotic and lentic water bodies positively influence species richness. Besides species richness, we evaluated species composition in microhabitats, testing if it is determined by the environmental characteristics of microhabitats or a consequence of water bodies spatial structure. In the second chapter, we seek to investigate the relationship between continuous and discontinuous environmental gradients - considering the environmental characteristics of lotic and lentic water bodies - with the taxonomic, phylogenetic and functional diversity of tadpoles on a local scale. The results of the first chapter show that species richness in microhabitats in lentic and lotic water bodies was influenced, respectively, by the amount of vegetation and sand. The aquatic vegetation had a positively relationship with tadpoles richness, probably due to the greater amount of food and refuge from predators provided. In lotic environments, the positive relationship of species richness with sand probably due to the selection of microhabitats with lower currents, where the sand is accumulated. In contrast, species composition in lentic and lotic microhabitats was mainly ...

Inúmeros processos tem sido sugeridos para explicar a estruturação de comunidades, como por exemplo competição, predação, dispersão, deriva continental, filtragem ambiental, especiação. A compreensão da influência desses processos em escala local é capaz de possibilitar uma melhor compreensão dos determinantes da composição e riqueza de espécies em comunidades, especialmente as bem delimitadas fisicamente, como é o caso das comunidades de girinos. Nosso objetivo neste estudo foi investigar a influência de características ambientais na estruturação de comunidades de girinos em corpos d'água lênticos e lóticos. Realizamos as amostragens em uma área de Mata Atlântica no sudeste do Brasil. Este trabalho está dividido em dois capítulos. No primeiro capítulo verificamos quais características ambientais dos microhabitats de corpos d'água lênticos e lóticos influenciam positivamente a riqueza de espécies. Além da riqueza, avaliamos ainda a composição de espécies nos microhabitats, testando se ela é determinada pelas características ambientais ou um reflexo da estrutura espacial dos corpos d'água. No segundo capítulo, investigamos a relação entre os gradientes ambientais contínuos e descontínuos - considerando as características ambientais de corpos d'água lênticos e lóticos - com a diversidade taxonômica, filogenética e funcional de girinos em escala local. Os resultados do primeiro capítulo demonstram que a riqueza de espécies nos microhabitats dos corpos d’água lênticos e lóticos foi influenciada, respectivamente, pela quantidade de vegetação e de areia. A vegetação aquática influenciou positivamente a riqueza, provavelmente por proporcionar maior quantidade de alimento e de refúgios contra predadores. Nos ambientes lóticos, a relação positiva da riqueza de espécies com o substrato arenoso provavelmente decorre da seleção de microhabitats com menor correnteza, onde a areia fica ...
Keywords: Ecologia animal; Girino - Mata Atlântica; Nicho (Ecologia); Ecossistemas; Biodiversidade; Animal ecology